Registro de Oligochaeta (Annelida: Clitelata) na Reserva Biológica de Pindorama - SP, Brasil (Revista Brasileira Multidisciplinar, 2022)
The establishment of Conservation Units is extremely important to reduce the effects of fragmentation and the consequent loss of biodiversity, however, it is also necessary to know the biological diversity protected by these areas. The objective of this study was to make a diagnosis aiming to contribute to the knowledge of the distribution and diversity of the Oligochaeta species in the Pindorama Biological Reserve, located in the northwest region of the State of São Paulo. The present study was carried out in four sampling sites of two forest fragments, inserted in the Reserve, in October 2020. The sediment samples for identification of the oligofauna were collected in triplicate on the depositional margin of each site, using type “D” net. Ten species were found distributed in three families, with Naididae being the most diverse composed by the species Allonais paraguayensis, Dero digitata, Dero evelinae, Pristina proboscídea, Pristina synclites and Slavina evelinae. Tubificidae, composed by the species Aulodrilus pigueti, Bothrioneorum sp. and Brinkhurstia americana. And Opistocystidae represented by only one species, Opistocysta serrata. These results are of great importance for the conservation of the biodiversity of forest fragments of the Atlantic Forest. In addition, studies involving the registration of species are necessary to increase knowledge of the local biodiversity, the Pindorama Biological Reserve and its region.
Keywords: Forest fragments. Biodiversity hotspot. Conservation Area. Macroinvertebrates.